The Philosophical Underpinnings of the Enhanced Critical Incident Technique - McDaniel, Matthew M.; Borgen, William A.; Buchanan, Marla J.; Butterfield, Lee D.; Amundson, Norm E. (Canadian Journal of Counselling and Psychotherapy, 2020)
Since its introduction in 1954, the critical incident technique (CIT) has been modified for use within counselling psychology and undergone several contemporary enhancements. While the method’s procedures and history have been described thoroughly, its philosophical underpinnings have not. This article seeks to fill this gap by contrasting the most current iteration of the CIT (i.e., the enhanced critical incident technique, or ECIT) across the philosophy of science paradigms. The ECIT is found to contain specific and rigorous post-positive epistemological elements and a flexible ontological position. This makes the ECIT a malleable method that can meet the needs of researchers from multiple perspectives.